0485 Environmental exposure to radiofrequency and risk of lymphoma subtypes. (21st August 2017) - Cocco, P; Satta, G; Salis, A; Saba, L; Sanna, S; Angelucci, E; Gabbas, A; Culurgioni, F; Pili, P; Mura, E; Cappai, M; Ennas, Maris G
Abstract : Introduction: Conflicting results have been published on the association between occupational and environmental exposure to radiofrequency (RF) and cancer risk Information bias might have played a role in some instances. Methods: We geocoded fixed radio-tv transmitters and mobile phone base stations, as well as the residence of 451 cases and 603 controls who participated in a case-control study on the aetiology of lymphoma in Sardinia, Italy. A detailed residential history was available for all cases and controls, including the perceived distance from fixed radio-tv transmitters and mobile phone base stations. We applied the models used by the Regional Agency for Environmental Protection, and conducted RF measurements to estimate the RF field at the door of study subjects. We used unconditional logistic regression to calculate Odds Ratios and their 95% confidence intervals for lymphoma and its major subtypes associated with the RF exposure metrics, adjusting by age, gender, and education. Results: Based on questionnaire data, risk of lymphoma overall was elevated for a cumulative exposure to fixed radio-tv transmitters above the median (OR=2.7, 95% CI=1.5–4.6). Risk was likewise elevated for all lymphoma subtypes. With reference to mobile phone base stations, we only observed a non significant excess risk of diffuse large B-cell lymphoma (DLBCL, OR=2.5, 95% CI=0.7–8.3). Such associations disappeared when we considered exposure based on the models, or the measurements. By comparing the reported distance to the geocoded data, we found out that the cases tended to underestimated the distance from the source of RF emission. Conclusions: Our results do not support the hypothesis of a link between environmental exposure to RF and risk of lymphoma subtypes. Conflict of Interest statement : None of the coauthors declare any conflict of interest related to the matters discussed in this paper.